Identification of Oudemansiella canarii and O. Cubensis (Basidiomycota, Physalacriaceae) in Argentina Using Morphological, Culture and Molecular Analysis - Alberti, Melisa; Niveiro, Nicolas; Zied, Diego Cunha [UNESP]; Albertó, Edgardo (Harvard University Botany Libraries, 2020)
Species of Oudemansiella are distributed worldwide mainly in tropical to south temperate zones. Morphological identification of the species is usually complex and may even be ambiguous, especially for O. canarii and O. cubensis, since they share many similar characters. They have been considered synonyms by several authors. There are no recent descriptions or detailed illustrations of Oudemansiella species from Argentina, and molecular data are practically null. In this work these species were described and illustrated making use of new collections, culture data, and nrITS phylogenetic analysis. It was not possible on the basis of the results to differentiate the species macroscopically, but these were differentiated at the microscopic level, mainly by their pileipellis structure. Phylogenetic analysis from nrITS sequences enabled the molecular identification of these two species, and the cultivation of basidiomes on lignocellulosic substrate allowed us to affirm that both species have a hemiangiocarpic development.
Keywords: Agaricales; Basidiomycota; ITS; phylogeny; taxonomy